The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/ijebr-01-2021-0067
|View full text |Cite
|
Sign up to set email alerts
|

The digital transformation of entrepreneurial work

Abstract: PurposeThis paper explores digital transformation's impact on the work of owners in entrepreneurial firms. The interplay between working practices and technology is analyzed, taking into account the organizations' specific contexts.Design/methodology/approachA multiple case study design was applied. Eight cases of entrepreneurial firms, defined as companies that bring new products and services to the market by creating and seizing opportunities, were selected, with the goal to maximize the diversity of cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…The second paper, "The digital transformation of entrepreneurial work" by Corvello et al (2021), focuses on the impact of digital transformation on the work of owners in entrepreneurial firms. The study examines the interplay between working practices and technology taking into account the organizations' specific contexts.…”
Section: Articles In the Simentioning
confidence: 99%
See 1 more Smart Citation
“…The second paper, "The digital transformation of entrepreneurial work" by Corvello et al (2021), focuses on the impact of digital transformation on the work of owners in entrepreneurial firms. The study examines the interplay between working practices and technology taking into account the organizations' specific contexts.…”
Section: Articles In the Simentioning
confidence: 99%
“…The second paper, “The digital transformation of entrepreneurial work” by Corvello et al . (2021), focuses on the impact of digital transformation on the work of owners in entrepreneurial firms.…”
Section: Articles In the Simentioning
confidence: 99%
“…More specifically, the pandemic crisis made entrepreneurs and managers realize that engagement in digital activities, especially those related to communication, is, in fact, a necessary strategic element of their daily work and operation (Corvello et al. , 2021) and not a luxury item, to be used occasionally.…”
Section: Introductionmentioning
confidence: 99%
“…Rosenblat and Stark ( 2016 ) have shown that digital technologies positively influence the employee-employer relationship in terms of autonomy and control, as they bring greater flexibility (Depaoli et al 2020 ). Digital technologies have a direct impact on the work of entrepreneurs and managers, which in turn affects SMEs performance and competitiveness (Corvello et al 2021 ; Secundo et al 2020 ). As for the external environment, digital technologies modify the processes through which SME entrepreneurs evaluate the environment in which they operate, identifying new opportunities and defining new strategies (Dellermann et al 2020 ; Scarmozzino et al 2017 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%